A estabilidade do servidor público e a burocracia temporária: estudo de caso dos professores de educação básica do estado de Minas Gerais - Espinola, Thaísa Ferreira Amaral Gomes (2022)
After the promulgation of the 1988 Constitution, there were changes in the concept of public service, as well as changes in the characteristics of the Brazilian public bureaucracy, such as the flexibilization of the stability of the public servant, these changes being reflections of the movement called New Public Management, defended by the Administrative Reform of 1995. However, permanent bureaucracy remained as a rule, occupying a position of effective provision, with temporary bureaucracy provided exceptionally. Since then, several other new proposals for modifying the characteristics and management of Brazilian public servants have emerged, such as the Administrative Reform of PEC no 32/2020, currently under debate in the National Congress. In general, proposals to change the characteristics of public bureaucracy focus on the institute of stability, seeking its flexibility or extinction, thus transforming a large part of the current stable public bureaucracy into temporary. The present research analyzed the influence of the public servant's stability in the policies and practices of people management, through the case study of a temporary and stable street level bureaucracy, represented by the Basic Education Teachers (PEB) of the state school system of State of Minas Gerais, from the point of view of its immediate superiors, the middle-level bureaucracy, the School Directors. The methodological procedures favored a qualitative approach, with a descriptive character, using data collection instruments from the literature review, documental research and interviews. The stability of the public servant, in general, is not perceived as a differentiating factor in the professional performance of the public servant and in determining the performance of PEB competencies, considering personal characteristics and management as determining factors in such variables. The lack of job stability was identified as harmful to the worker's mental health and as an impediment to the feeling of organizational belonging, which influences the behavior of public servants and their organizational dedication. In relation to administrative discontinuity, the high turnover of personnel generated by the lack of stability is seen as a factor that contributes to the rupture in management, compromising institutional results and preventing the improvement of people management policies and practices, and consequently, a higher quality public service. The stability of the civil servant, therefore, in general, positively influences people management practices and policies in the public sector and is still seen as attractive for joining the public service due to the economic security it provides. However, it was stressed the importance of effective management and the existence of effective instruments that make it possible to measure the performance of the server, as well as effectively apply the termination measures, in case of unsatisfactory performance, or of awards, in case of excellent performance.